39+4y-16=17y-13-4y

Simple and best practice solution for 39+4y-16=17y-13-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39+4y-16=17y-13-4y equation:


Simplifying
39 + 4y + -16 = 17y + -13 + -4y

Reorder the terms:
39 + -16 + 4y = 17y + -13 + -4y

Combine like terms: 39 + -16 = 23
23 + 4y = 17y + -13 + -4y

Reorder the terms:
23 + 4y = -13 + 17y + -4y

Combine like terms: 17y + -4y = 13y
23 + 4y = -13 + 13y

Solving
23 + 4y = -13 + 13y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-13y' to each side of the equation.
23 + 4y + -13y = -13 + 13y + -13y

Combine like terms: 4y + -13y = -9y
23 + -9y = -13 + 13y + -13y

Combine like terms: 13y + -13y = 0
23 + -9y = -13 + 0
23 + -9y = -13

Add '-23' to each side of the equation.
23 + -23 + -9y = -13 + -23

Combine like terms: 23 + -23 = 0
0 + -9y = -13 + -23
-9y = -13 + -23

Combine like terms: -13 + -23 = -36
-9y = -36

Divide each side by '-9'.
y = 4

Simplifying
y = 4

See similar equations:

| 6(x+4)-9=2x+4(5+x) | | y-5=-5(x+6) | | 20x-16=20x+7 | | 4(x+12)-(6n+6)= | | 2x+7y=k+8 | | 3y^2+65=2y^2+127 | | 20x-16=20x+4 | | 0.85x+0.05(10-x)=0.10(-27) | | -7(3x-3)+6=-21x+27 | | 3x^2+3y^2+15y+9x+12=0 | | 2x(3x-9)-4=2(x-3) | | 6(18.5)-3=x | | 11r^2+28=0 | | -7(3x-3)+6=-21x+7 | | (5+x^4)-(3x^4+4x)=0 | | h(x)=x^2+9x+8 | | 2(-3y-1)+(2y+7)=a | | 2x+5+6x-3+30=180 | | 40.7=5b | | -3(x+9)+6x=-6 | | 3(x^3+2x^2+8x+36)=0 | | -9d-8=154 | | -0.10(13)+0.20x=0.05(x-14) | | 5(3x-6)-4=5(x-4)+76 | | 8n^2=24n+320 | | Y-8=37-7y | | 5ab+7ac-ab+3ab= | | 20x-16=20x+16 | | 4y+0.5x=12 | | 0.12y+0.06(y+3000)=720 | | -1(1+7y)-6(-7-x)=36 | | Tan(5x)=10 |

Equations solver categories